TEST RIG FOR EXPERIMENTAL INVESTIGATION OF THE DYNAMIC CHARACTERISTICS OF FLEXIBLE PIPELINES - Purdik, Victor; Pozdniakov, Mykhailo (Scientific Works of Vinnytsia National Technical University, 2015)
This work deals with experimental verification of the dynamic characteristics of high-pressure sleeves. The paper contains design circuit of the test installation based on 3D model and description of the test procedure. Also, relationships are presented, which make it possible to calculate the value of the main dynamic indicator – the compliance coefficient. REFERENCES 1. Рукава резиновые высокого давления с металлическими оплетками неармированные. Технические условия : ГОСТ 6286-73. – [Чинний від 1974-07-01]. М.: ИПК Издательство стандартов, 2003. – 16 с. 2. Рукава высокого давления армированные для гидросистем тракторов и сельскохозяйственных машин. Основные параметры и присоединительные размеры : ГОСТ Р 51207-98. – [Чинний від 2000-01-01]. М.: ИПК Издательство стандартов, 1999. – 7 с. 3. Немировский И. А. Расчет гидроприводов технологических машин / И. А. Немировский. – К.: Техника, 1992. – 181 с. 4. Дусанюк Ж. П. Дослідження динамічних характеристик рукавів високого тиску / Ж. П. Дусанюк, О. В. Дерібо, В. І. Савуляк, С. В. Дусанюк // Вісник ВПІ. – 1998. – № 1. – С. 83 – 87 5. Ishikawa K. Experimental study on dynamic pipe fracture in consideration of hydropower plant model / K. Ishikawa, Y. Kono, A. Haga, K. Kato, K. Sugawara // Annual Journal Water Science and Engineering. – 2009. – № 2(4). – P. 60 – 68. 6. George E. Tolten. Tribology of hydraulic pump testing / George E. Tolten, Gary H. King, Donald M. Smolenski. – Philadelphia.: (STP: 1310). – 1997. – 376 p. 7. Rowinski Pawel. Experimental Methods in Hydraulic Research / Pawel Rowinski. – Berlin: Springer-Verlag Berlin Heildelberg. – 2011. – 321 p. 8. George E. Tolten. Hydraulic failure analysis: fluids, components and system effects / George E. Tolten, David K. Wills, Dierk G. Feldmann. – Philadelphia: (STP: 1339). – 2001. – 601 p. 9. Pat. 5,481,902 United States Patent МПК6 G01M 3/02, G01M 3/28. Pipe Testing system / Douglas Lanasa. — Claimer and patent holder Lanasa; Douglas (Channelview, TX). – №08/188,023; claimed 28.01.94 ; published 09.01.96. 10. Pat. 4,442,403 United States Patent МПК6 G01N 27/90, G01N 027/72, G01N 027/82. Testing installation for pipes having an internal testing unit driven by the rotation of the pipe/ Carl-Ludwig Pohler. — Claimer and patent holder Pohler; Carl-Ludwig (D-5650 Solingen 1, DE). – №06/249,887; claimed 01.04.81 ; published 10.04.84.